We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
+2
263
1
avatar

\({5x-2\over x+3} = 5 - {17 \over x+3}\)

 Feb 12, 2018
 #1
avatar+101761 
+2

\({5x-2\over x+3} = 5 - {17 \over x+3}~\\ \qquad 5(x+3)=5x+15\\ LHS\\={5x-2\over x+3}\\={5(x+3)-15-2\over x+3}\\={5(x+3)-17\over x+3}\\= {5(x+3)\over x+3}-{17\over x+3}\\= 5-{17\over x+3}\ \)

 

This is not really what you were expected to do though.

You were expected to do algebraic division or synthetic division

 

This is an example of what you were supposed to do :)

 

https://www.youtube.com/watch?v=H94ma2ofGuc

 Feb 12, 2018

14 Online Users

avatar
avatar